Economic burden of varicella in Europe in the absence of universal varicella vaccination - Manjiri Pawaskar; Estelle Méroc; Salome Samant; Elmira Flem; Goran Bencina; Margarita Riera-Montes; Ulrich Heininger (BMC, 2021)
Abstract Background Though the disease burden of varicella in Europe has been reported previously, the economic burden is still unknown. This study estimated the economic burden of varicella in Europe in the absence of Universal Varicella Vaccination (UVV) in 2018 Euros from both payer (direct costs) and societal (direct and indirect costs) perspectives. Methods We estimated the country specific and overall annual costs of varicella in absence of UVV in 31 European countries (27 EU countries, plus Iceland, Norway, Switzerland and the United Kingdom). To obtain country specific unit costs and associated healthcare utilization, we conducted a systematic literature review, searching in PubMed, EMBASE, NEED, DARE, REPEC, Open Grey, and public heath websites (1/1/1999-10/15/2019). The number of annual varicella cases, deaths, outpatient visits and hospitalizations were calculated (without UVV) based on age-specific incidence rates (Riera-Montes et al. 2017) and 2018 population data by country. Unit cost per varicella case and disease burden data were combined using stochastic modeling to estimate 2018 costs stratified by country, age and healthcare resource. Results Overall annual total costs associated with varicella were estimated to be €662,592,061 (Range: €309,552,363 to €1,015,631,760) in Europe in absence of UVV. Direct and indirect costs were estimated at €229,076,206 (Range €144,809,557 to €313,342,856) and €433,515,855 (Range €164,742,806 to €702,288,904), respectively. Total cost per case was €121.45 (direct: €41.99; indirect: €79.46). Almost half of the costs were attributed to cases in children under 5 years, owing mainly to caregiver work loss. The distribution of costs by healthcare resource was similar across countries. France and Germany accounted for 49.28% of total annual costs, most likely due to a combination of high numbers of cases and unit costs in these countries. Conclusions The economic burden of varicella across Europe in the absence of UVV is substantial (over 600 M€), primarily driven by caregiver burden including work productivity losses.